Pengenalan literasi media untuk pencegahan konflik sosial pada siswa sekolah dasar di wilayah perdesaan - Leadya Raturahmi; R. Ismira Febrina; Rosanti Utami Dewi SY (University of Islam Malang, 2021)
Human development in the field of education is very important because it relates to the quality of human life in other fields, one of which is on the social aspects, especially those related to children. The condition that occurs in children today is the high use and negative exposure of mass media, especially from the use of television and the internet. The high use of this media is not accompanied by adequate skills in children regarding access and ability to analyze the content of media messages so that negative impacts of use appear, including social conflicts between children in their environment. The purpose of this activity is to introduce the ability to access, analyze, evaluate and communicate messages in various forms of communication and information media for the prevention of social conflict in children. The method of carrying out activities using lecture, demonstration, and discussion methods. The subject of the activity is elementary school age children in Panembong Village, Bayongbong District, Garut Regency. The implementation process is carried out with the assessment stage, the implementation stage, and the assessment stage as well as the evaluation stage. The results of this activity illustrate the existence of better knowledge and understanding of elementary school age children in accessing, analyzing, evaluating and communicating messages in various forms of communication and information media, especially to prevent social conflict between peers.